Should I Plan to Open? Predicting the Need for Open Reduction in the Treatment of Developmental Dysplasia of the Hip. Issue 5 (May 2020) - Talathi, Nakul S.; Trionfo, Arianna; Patel, Neeraj M.; Upasani, Vidyadhar V.; Matheney, Travis; Mulpuri, Kishore; Sankar, Wudbhav N.
Abstract : Background: Closed reduction is generally attempted on children under 18 months of age who present as older infants or who fail nonoperative management for developmental dysplasia of the hip (DDH). However, many of these patients will not achieve concentric reduction by closed means and will ultimately require open reduction (OR). Limited evidence exists to predict which patients can be adequately closed reduced versus those who will need open treatment. Methods: Prospectively collected data from 4 select centers of an international multicenter study group sharing a common treatment approach were reviewed for all DDH infants under 18 months old that required operative management. Patients were categorized into 2 groups: those whose hips were successfully closed reduced or those who ultimately required OR. Factors were compared between the closed reduction and OR groups for 2 separate cohorts—those presenting early in life with ultrasound (US) data, and those presenting later with radiographic data. Results: A total of 154 patients (166 hips) were included in the analysis. Overall, 87.3% were female. In the early-presenting cohort, purposeful entry multivariate regression revealed that patients with Graf IV hips on US had 3.8 times higher odds of requiring an OR. For the later cohort, hips that were clinically irreducible (ie, negative Ortolani sign) had 3.3 times higher odds of requiring OR. Patients with International Hip Dysplasia Institute (IHDI) grade IV hips had 2.5 times higher odds of needing an OR versus those with grade III hips and 15.4 times higher odds than those with grade II hips. Children with an IHDI grade IV hip and a negative Ortolani sign had 4.4 times higher odds of needing OR. Conclusion: Children younger than 18 months with dislocated hips who require OR are more likely to have a high-grade radiographic dislocation (IHDI grade IV), negative preoperative Ortolani sign, and a Graf IV classification on initial US. This information may help surgeons budget the use of operating room time and better counsel parents about intraoperative expectations. Level of Evidence: Level III—Prognostic.